Penyelesaian Sengketa Rumah Tangga di Luar Pengadilan Menurut Hukum Islam - Iman Jauhari (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: This research aims to explore the domestic dispute of husband and wife and how to solve it through non litigated settlement based on sharia law. The method applied is content analysis fro the relevant sources of the research. The dispute results from the lack of understanding of the couple regarding the value of marriage based on Islamic law. The divorce might be resulted from economy, infidelity, and education background factors, whil the percentage is 90% whil domestic violence, drinking and gambling factors have te percentage of 10%. The settlement could be coducted through peaceful way by appointing one mediator both from husband and wife sides. This concept based on the 35, An-Nisa Chapter of the holy Quran suggesting that it is recommended the family dispute could be solved peacefully and accepted by both parties. The mediaton phase conducted by hakam is the second phase while the parties themselves solve the first one. Such second process is called non litigation settlement, which takes short time, accepted by the parties and keeps the confidental of the conflicting parties. The Non Litigation Settlement of Family Dispute Based on Islamic Law